(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2015)
The reaction of α-azolyl-2-hydroxyacetophenones with chloroacetyl chloride in acetonitrile in the presence of pyridine resulted in 2- chloromethyl-3-azolylchromones, while both the α-(2-pyridyl) and α-(2-quinolyl) derivatives formed the products of the subsequent intramolecular cyclization with annelation of indolizine or pyrroloquinoline ring to the chromone core.